National Culture, Families, or Education Policies: What Determines National Test Scores? (2017)
Conventional analyses attribute cross-country differences in students’ average test scores to family characteristics, school resources, and school system characteristics, but institutional economists and cultural anthropologists argue that cultural beliefs and institutions are the fundamental determinants of a society’s level of human capital. I examine the effects of cultural beliefs, institutional characteristics, family characteristics, and various school and education policy characteristics on average PISA scores in mathematics. I find that national cultural and institutional characteristics explain over 80% of the variation in average scores across 58 countries. When family, school, and school system characteristics are included as causes, cultural and institutional characteristics continue to explain most of the variation in average scores. More financial resources for schools continue to raise average scores, the existence of a central exit exam has a small effect, and the share of private enrollment in the school system has no effect on these scores.